Non-adaptedness and vulnerability to climate change threaten Plathymenia trees (Fabaceae) from the Cerrado and Atlantic Forest - André Carneiro Muniz; José Pires de Lemos-Filho; Maria Bernadete Lovato (Scientific Reports)
Abstract Climate change is increasing species extinction risk. The ability of a species to cope with climate change can be quantified by projecting distribution models and by estimating the risk of non-adaptedness using genomic data. The Cerrado and the Atlantic Forest in Tropical South America are increasingly threatened by habitat loss and anthropogenic climate change. This work aims to evaluate the ecological and genomic vulnerability of Plathymenia taxa and its lineages, P. reticulata, a Cerrado species, and P. foliolosa, an Atlantic Forest species, to determine their current and future habitat suitability and the mismatch between current local adaptation with the expected climate changes. The species distribution models predicted a high range loss for the Plathymenia lineages. The genotype-environment association analyses showed that the Plathymenia lineages have populations adapted to different precipitation and temperature seasonality regimes. The genomic offset analyses predict a mismatch between local adaptations and future climate for the Plathymenia indicating a high risk of non-adaptedness, especially in the pessimistic scenario. Our results show an elevated extinction risk of the species due to climate change. We suggest reevaluating the extinction risk and management of the Plathymenia species separately based on their differences in vulnerability to climate change.